MEDIA, EDUCATION AND THE DEVELOPMENT OF EDUCATION IN HUMAN RIGHTS - Oliveira, Flaviana de Freitas [UNESP]; Klein, Ana Maria [UNESP] (Fundacao Univ Tocantins, 2020)
Media is an important mediating agent in democratic societies, being responsible for a dialectical process with the spectator that involves social, political, economic and cultural spheres. In this way, the media has high potential for education, as a formation of citizenship of the individual. National plans and guidelines consider the media as one of the necessary axes for Human Rights Education. Television, in this context, is the main media vehicle of the country, as it is widely used in the daily life of Brazilians. It is important to mention the importance of newscasts, which have the value of credibility and are relevant informal educators. This article aims to analyze the role of the media in contemporary society, more specifically the newscasts, considering its possible contribution to Human Rights Education. As a research method, bibliographic research was used, considering works in Portuguese and Spanish published since the 2000s, in addition to works produced in the 20th century for sociological concepts and theories. It was found that the media can contribute to knowledge or prejudice about Human Rights. Critical reading of the media, in this process, is essential to prevent users from simply reproducing prejudices or distorted ideas, without due critical analysis of the contents disclosed or omitted.
Keywords: Media; Mediation; Human Rights; Television; Informal Education